English pitstop / Choo Kim Fong and Muhammad Imran Rosli - Kim Fong, Choo; Rosli, Muhammad Imran (Academy of Language Studies, 2023)
English Pitstop (EP) is an innovative project designed to help people learn and appreciate the English language. Through the official Instagram page, users can interact with different visuals, such as short videos, posters, and memes, all related to English. This project aims to be a well known Instagram page in Malaysia and the first one that comes to mind when people think of an educational page. EP is a great way for English learners at any level to expand their knowledge and have fun while doing so. This project is sure to be an exciting and educational experience for all those who are passionate about English.